Pengaruh Pupuk NPK Phonska terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays saccharata Sturt.) - Emanuel Fidelis Leba; Hendrikus Darwin Beja; Mario Malado (Agriculture - Jurnal Ilmu Pertanian, 2026)
This study was conducted at the Perumnas Maumere Scout Camp from June to August 2025. Corn, or Zea mays L., is one of Indonesia’s staple foods after rice; as a cereal crop, corn can be grown from lowlands up to mountainous regions at elevations between 1,000–1,800 meters above sea level. Areas with an optimal elevation of 0–600 m above sea level are ideal for corn growth. The objective of this study is to determine the effect of Phonska NPK fertilizer on the growth and yield of sweet corn (Zea mays saccharata sturt.) and to determine the optimal dose of Phonska NPK fertilizer for the production of sweet corn (Zea mays saccharata sturt.). The method used in this study was a randomized block design (RBD) with five treatments and four replications, namely: PK0: 0 kg/ha, PK1: 200 kg/ha, PK2: 300 kg/ha, PK3: 400 kg/ha, and PK4: 500 kg/ha. Based on the results of the analysis of variance using a randomized block design (RBD), the study found that the effect of NPK Phonska fertilizer application on the growth and yield of sweet corn had a significant effect on plant height at 21 days after sowing (das), the number of leaves at 21 days after sowing (das), cob length, and cob diameter, and had no significant effect on plant height at 42 days after sowing (das), the number of leaves at 42 days after sowing, dry kernel weight per plant, and dry kernel weight per hectare. The optimal application rate of NPK Phonska fertilizer at 200 kg/ha was the best treatment for optimal growth and yield of sweet corn (Zea mays saccharata Sturt.).